2012
DOI: 10.1007/s00128-012-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Vitamin A and its Metabolites in Rat Testis: Possible Involvement of Vitamin A in Testicular Toxicity Caused by Molinate

Abstract: This study was conducted to evaluate the effect of molinate on retinoids homeostasis in rat testis. Molinate was administrated to male Sprague–Dawley rats (200 mg kg−1 in corn oil, ip). Retinoid measurements were made at 6, 12, 48 and 168 h time points after administration. Testis levels of retinoic acid decreased (32 %) in a statistically significant manner at the 12 and 48 h time points. However, retinol and retinaldehyde were not significantly affected by molinate. These results suggest that molinate affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Retinoic acid captures free radicals without interacting with biological targets and prevents free radical formation with its chain-breaking effect. Retinoic acid prevents lipid peroxidation in cellular membranes [8], and also has anti-proliferative, anti-inflammatory, and anti-cancer effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…Retinoic acid captures free radicals without interacting with biological targets and prevents free radical formation with its chain-breaking effect. Retinoic acid prevents lipid peroxidation in cellular membranes [8], and also has anti-proliferative, anti-inflammatory, and anti-cancer effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are no reports of molinate being a developmental toxicant, though it is known to cause testicular toxicity and sperm damage and thus to impair male fertility [17]. It has been suggested that molinate acts by inhibiting retinoic acid synthesis [18]. Retinoic acid itself activates the Wnt signaling pathway in our assay while molinate produced an inhibitory effect.…”
Section: False Positivesmentioning
confidence: 87%